Feedforward Enhanced Control System to Pursue Mathematical Competencies Achievement in Engineering Education - Francisco Mínguez-Aroca; Santiago Moll-López; Nuria Llobregat-Gómez; María-Dolores Roselló; Luis M. Sánchez-Ruiz (MDPI AG, 2024)
The learning process can be conceptualized as a dynamic system constantly evolving and adapting in response to a variety of stimuli and inputs. This paper presents a novel approach to competency-based assessment that integrates a dynamic assignment design of personalized activities with the aid of a 3D matrix array structure. This structure, named Topic, Activity, and Competency (TAC) cuboid, provides a detailed view of the student's progress, enabling the design of tailored curricular strategies to facilitate the development of competencies. Personalized activities serve as control inputs that adapt to each learner's state, driving a feedforward that promotes proactive improvement. An automation process becomes necessary to cope with the increased data volume from the TAC cuboid and the information complexity. The concept model registers TAC cuboid information, enabling a dynamic analysis to forward an adequate workload when required to facilitate students' achievement of their expected mathematical competencies. Additionally, the paper discusses the initial application of these models in an educational role-playing game, demonstrating their effectiveness in a gamified learning environment.